La valutazione del capitale intellettuale - Giuliani, Marco (Sistemi Informativi, Management e Controllo - Open Access, 2017)
Intellectual capital is gaining in importance over the years, evolving from a "needed to win" resource, necessary to control the market, into a "needed to play" resource, namely an essential element for the survival of the firm. This evolution has led to innovations in accounting concepts, methods and tools. This work offers a critical analysis of the main methods and tools for the evaluation of the intellectual capital, of the potentials and limits of the various evaluation models proposed by the doctrine and the practice. A business case study completes the book.